2020
DOI: 10.1002/ece3.7087
|View full text |Cite
|
Sign up to set email alerts
|

Are British urban foxes (Vulpes vulpes) “bold”? The importance of understanding human–wildlife interactions in urban areas

Abstract: There is a widespread perception that interactions between people and wildlife are increasing as human populations and urban areas expand. This is of particular concern with carnivores (Curtis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 69 publications
(111 reference statements)
2
8
0
Order By: Relevance
“…Since foxes were willing to consume the food rewards when novel objects were absent, it also rules out the possibility that food-related motivation explains why foxes avoided the objects. Finally, as reported in Padovani et al (2021), we found in our larger multisite sample no seasonal differences in foxes' responses to novel objects, which rules out seasonal differences in food abundance, and hence, variation in their motivation due to hunger.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Since foxes were willing to consume the food rewards when novel objects were absent, it also rules out the possibility that food-related motivation explains why foxes avoided the objects. Finally, as reported in Padovani et al (2021), we found in our larger multisite sample no seasonal differences in foxes' responses to novel objects, which rules out seasonal differences in food abundance, and hence, variation in their motivation due to hunger.…”
Section: Discussionsupporting
confidence: 82%
“…Factors, such as speed of habituation, may be crucial for them to overcome their aversion to such novelty (Vincze et al, 2016). Age, sex, dominance, associative learning, and/or personality are also some of the many other factors that might influence foxes' decision-making (Fawcett et al, 2017;Griffin et al, 2013;Padovani et al, 2021;Soulsbury et al, 2011a). As previously discussed, foxes may simply prefer to exploit easy-access resources wherever possible, similar to what has been proposed for challenging tasks in some populations of wild raccoons (Procyon lotor) (Morton, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Red foxes have shown to be adaptable enough to be able to deal with these stimuli and therefore have been able to take advantage of anthropogenic foods on offer. In urban areas, their densities are typically much higher (Harris & Rayner, 1986), they can live and breed in residential back gardens (Padovani et al, 2021), have become more nocturnal (Gil-Fern andez et al, 2020), and have even been shown to change morphologically to develop traits normally associated with domestication (Parsons et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…These interactions have been documented in multiple species across terrestrial, aquatic and aerial environments (Brookhouse et al, 2013; Dayer et al, 2019; Padovani et al, 2021; Pagel et al, 2020; Usui & Funck, 2018), with national and public parks being popular targets (Marion et al, 2008). Humans risk injury from these interactions as animals become accustomed to utilising humans as a food source (Burns & Howard, 2003; Kofron, 1999) and disease transfer is also an associated risk (either directly, e.g.…”
Section: Introductionmentioning
confidence: 99%